Interiors in flux : the coexistence of existing building stock and mass timber through adaptive reuse for environmental sustainability and user well-being - Van der Hoven, Christo (University of Pretoria, 2024)
Mini Dissertation (MIntArch (Prof))--University of Pretoria, 2024.